The contemporary law of targeting : [military objectives, proportionality and precautions in attack under additional Protocol I] - Henderson, Ian (International humanitarian law series, 2009)
Armed conflict is about using force to achieve goals. As international humanitarian law regulates the means and methods that a belligerent may adopt to achieve its goals, there will inevitably be disagreements over the interpretation of that law. As for the rules that regulate targeting, the main difficulties arise over what is a lawful target and what is proportional collateral damage. This book provides a detailed analysis of those issues. Also, a chapter is dedicated to considering how United Nations Security Council sanctioning of participation in an armed conflict might affect the range o.